Recent advances in clinical practice: management of inflammatory bowel disease during the COVID-19 pandemic. Issue 7 (27th April 2022) - Lin, Simeng; Lau, Louis HS; Chanchlani, Neil; Kennedy, Nicholas A; Ng, Siew C
Abstract : The COVID-19 pandemic has raised considerable concerns that patients with inflammatory bowel disease (IBD), particularly those treated with immunosuppressive therapies, may have an increased risk of SARS-CoV-2 acquisition, develop worse outcomes following COVID-19, and have suboptimal vaccine response compared with the general population. In this review, we summarise data on the risk of COVID-19 and associated outcomes, and latest guidance on SARS-CoV-2 vaccines in patients with IBD. Emerging evidence suggests that commonly used medications for IBD, such as corticosteroids but not biologicals, were associated with adverse outcomes to COVID-19. There has been no increased risk of de novo, or delayed, IBD diagnoses, however, an overall decrease in endoscopy procedures has led to a rise in the number of missed endoscopic-detected cancers during the pandemic. The impact of IBD medication on vaccine response has been a research priority recently. Data suggest that patients with IBD treated with antitumour necrosis factor (TNF) medications had attenuated humoral responses to SARS-CoV-2 vaccines, and more rapid antibody decay, compared with non-anti-TNF-treated patients. Reassuringly, rates of breakthrough infections and hospitalisations in all patients who received vaccines, irrespective of IBD treatment, remained low. International guidelines recommend that all patients with IBD treated with immunosuppressive therapies should receive, at any point during their treatment cycle, three primary doses of SARS-CoV-2 vaccines with a further booster dose as soon as possible. Future research should focus on our understanding of the rate of antibody decay in biological-treated patients, which patients require additional doses of SARS-CoV-2 vaccine, the long-term risks of COVID-19 on IBD disease course and activity, and the potential risk of long COVID-19 in patients with IBD.